Geotechnical properties of products of alternative fuel combustion and co-firing with hard coal in the context of their use as solidifying dense mixtures. Issue 12 (December 2018) - Stefaniak, Sebastian; Kmiecik, Ewa; Miszczak, Ewa; Plewa, Franciszek; Twardowska, Irena
Efforts directed to reduction of greenhouse gas emissions have led to the introduction of new firing/co-firing technologies and alternative fuels in the coal-based power industry. This has resulted in the formation of combustion products with new properties that can affect the reuse of these wastes and/or pose a hazard to the environment. One of the power-plant fly ash (FA) reuse options is its application as a solidifying dense mixture with water for backfilling mine workings or in engineering constructions. In this comparative study, geotechnical properties of three groups of FA were evaluated: (i) weathered and freshly generated ash from hard coal combustion in conventional pulverized coal boilers without (C-PCA, C-PFA) and with selective non-catalytic reduction installations for NO x reduction (NC-PFA); (ii) FA from hard coal co-firing with alternative fuels: off gases (GC-PFA) or biomass (BC-PFA) in pulverized coal boilers; (iii) FA from coal (C-FFA) or biomass combustion (B-FFA) in fluidized-bed boilers. The transportability, bonding and solidification properties, uniaxial compression strength, and rewetting of dense mixtures were evaluated by measurements of volumetric density, fluidity, water retention capacity, bonding time, solidification time, uniaxial compression test, and slakeability at the background of the FA chemical composition. Calcareous C-FFA> B-FFA displayed the best geotechnical properties. Other materials showed poorer geotechnical properties than FFA and could be aligned in the order BC-PFA> GC-PFA> NC-PFA> C-PFA> C-PCA.